## (click here to return)

If 4x + 3 = 11, then x = 2.

Proof:

4x + 3 = 11

if, and only if,

(4x + 3) - 3 = 11 - 3

if, and only if,

4x = 8

if, and only if,

(4x)/4 = 8/4

if, and only if,

x = 2

Therefore, 4x + 3 = 11 if, and only if, x = 2.

Therefore, if 4x + 3 = 11, then x = 2.

(end of page)

4x + 3 = 11

if, and only if,

(4x + 3) - 3 = 11 - 3

if, and only if,

4x = 8

if, and only if,

(4x)/4 = 8/4

if, and only if,

x = 2

Therefore, 4x + 3 = 11 if, and only if, x = 2.

Therefore, if 4x + 3 = 11, then x = 2.

(end of page)